2018
DOI: 10.4028/www.scientific.net/kem.763.1147
|View full text |Cite
|
Sign up to set email alerts
|

Remarks on Seismic Design Rules of EC8 for Inverted-V CBFs

Abstract: Chevron concentrically braced frames (C-CBFs) are expected to provide limited ductility in the framework of Eurocode 8: differently from North American codes, lower values of behavior factors are recommended by EN 1998 for C-CBFs than for other concentric bracing configurations (namely diagonal and cross bracings). The research presented in this paper is aimed at revising the design rules and requirements provided for by EN 1998-1 for C-CBFs in order to improve the ductility and the dissipative capacity of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…As highlighted by previous research [17][18][19], the force transfer mechanism in the post-buckling range differs significantly from the elastic behavior and the columns are likely be subjected to a force significantly larger than that calculated according to Equation (11).…”
Section: Chevron Concentrically Braced Frames (Ccbf)mentioning
confidence: 93%
See 2 more Smart Citations
“…As highlighted by previous research [17][18][19], the force transfer mechanism in the post-buckling range differs significantly from the elastic behavior and the columns are likely be subjected to a force significantly larger than that calculated according to Equation (11).…”
Section: Chevron Concentrically Braced Frames (Ccbf)mentioning
confidence: 93%
“…The seismic performance of chevron concentric bracings depends significantly on the behaviour of the brace-intercepted beam [17,29,30]. Indeed, after the buckling of the compression diagonal, an unbalanced vertical force is applied at the brace-intercepting section, inducing high bending demand.…”
Section: Chevron Concentrically Braced Frames (Ccbf)mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous researchers [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] critically discussed and revised the design rules codified within EN 1998-1 and even identified some issues needing upgrading and/or amendment.…”
Section: Introductionmentioning
confidence: 99%
“…Another critical aspect of EC8-compliant design is related to the requirement on the capacity-to-demand ratios Ωi= Npl,br,Rd,i/NEd,br,i (being Npl,br,Rd,i the brace yield strength and NEd,br,i the design forces due to the seismic actions) which should vary in the range (Ω; 1.25Ω) to guarantee uniform distribution of plasticity along the building height and thus mitigating the tendency of CBFs to soft-story mechanisms. Several Authors [11][12][13][14][15][16][17][18] showed that this requirement is not adequate to guarantee an overall plastic engagement of the dissipative elements and it also leads to oversize the diagonals at lower and intermediate stories. Indeed, to contemporarily satisfy the requirements of slenderness limits and the overstrength variation often leads to impractical solutions with significant difficulties to select the proper member for braces, being both requirements closely interrelated and juxtaposed [4-9, 11-12, 14-15].…”
Section: Introductionmentioning
confidence: 99%